2015
DOI: 10.1111/apt.13423
|View full text |Cite
|
Sign up to set email alerts
|

Smoking behaviour and knowledge of the health effects of smoking in patients with inflammatory bowel disease

Abstract: SUMMARY BackgroundThe detrimental effect of smoking on development and progression of Crohn's disease (CD) is generally accepted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…16,18 Studies in non-IBD populations have found that smoking initiation is more likely when there is a perceived short-term benefit, despite acceptance of short-and long-term risks. Furthermore, we found no evidence that smoking cessation impacts adversely on subsequent clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,18 Studies in non-IBD populations have found that smoking initiation is more likely when there is a perceived short-term benefit, despite acceptance of short-and long-term risks. Furthermore, we found no evidence that smoking cessation impacts adversely on subsequent clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…18 Data from the Swiss IBD Cohort found that only 2.6% of smokers with UC received any support to cease smoking, suggesting clinicians may be hesitant to recommend smoking cessation to patients with UC. 18 Data from the Swiss IBD Cohort found that only 2.6% of smokers with UC received any support to cease smoking, suggesting clinicians may be hesitant to recommend smoking cessation to patients with UC.…”
Section: Findings In Relation To Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies demonstrated that only one-third to one-half of patients with Crohn's disease were aware that smoking could worsen their prognosis ( 17,18 ). Patients who were actively smoking were the least informed ( 17 ).…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…1 The authors examined patient-awareness of the effects of smoking on the natural history of inflammatory bowel disease (IBD). The majority of IBD patients seemed unaware of the fact that smokers have an increased risk of developing Crohn's disease, an increased likelihood of requiring surgery, and higher rates of recurrence after surgery.…”
mentioning
confidence: 99%